Prospects and directions of digital transformation of Russian oil and gas companies - A. S. Flaksman; N. G. Lyubimova (Вестник университета)
The article analyzes the current state of digital technologies in industry in general and in the oil industry in particular. To understand the essence of digitalization, the authors consider some of the provisions set out in the state program “Digital Economy of the Russian Federation”. Relevant digital technologies are proposed for use for each stage of the oil cycle, considering the technological and economic features, and the possibility of introducing digital technologies into the business processes of oil and gas companies is assessed. In the final part of the article, based on the analysis of the prospects for the implementation of digital economy technologies in oil and gas companies, the results from the implementation of these technologies are identified, which manifest themselves both in the financial aspect and in intangible assets. At the same time, the article also identifies the most significant risks associated with the implementation and operation of business processes based on digital technologies.